Blind recognition of short linear block code based on the weight of common polynomial - Lihua SHEN; Jianlin ZHANG (Dianxin kexue)
According to the problem of a short linear block code in communication signal processing,an algorithm based on the maximal weight of common polynomial was proposed.Firstly,the received code sequence was divided with different lengths.Then the common polynomial of code words and xn+1 was obtained and filtered.The code length was estimated by the number of common polynomials.The weight was defined according to the probability of polynomial,and the generator polynomial was recovered according to the maximal weight.The validity and the performances of the blind recognition method were illustrated by the computer simulation results.The correct recognition rate of the algorithm is higher than that of the existing algorithms under the same bit error rate,and the method is applicable for both short codes and normal codes.